Quality assessment of microsimulation models: The case of EUROMOD - Holly Sutherland (University of Essex, Institute for Social and Economic Research (ISER), 2018)
Assessing the quality of microsimulation models is an important contributing factor for motivating their use in both academic and policy environments. This is particularly relevant for EUROMOD, the tax-benefit microsimulation model for the European Union, because it is intended to be widely used. This paper explains how the quality of EUROMOD is assessed. It focusses on the validity and scope of results as particularly important dimensions of quality, and on the transparency with which this assessment is done. It also provides evidence on the extent and breadth of the use of EUROMOD. Some of the key trade-offs between different aspects of quality are identified and the paper concludes with a view on the appropriate division of responsibility for quality assessment, between model developers and users.
Keywords: H31; C81; C88; 330; Tax-Benefit Microsimulation; Quality Assessment; European Union; EUROMOD